(EASTERN) SUMBA AND ITS GENRES OF ORAL TRADITION - Retang Wohangara (Soegijapranata Catholic University, 2006)
This paper provides some information on the island of Sumba and its people. As a cultural community not possessing a writing system, the Sumbanese people preserve and transmit their tradition-based creations such as language, literature, music, games, mythology, and rituals, for generations through oral communications. The peoples oral traditions, taking forms in some genres, have become inseparable parts of their lives. Though the vocabularies in daily usage are the same with the ones used in special occasions, for instance, in rituals, the metaphorical construction of language of the latter demands special attention.